Оптимізація алгоритму створення динамічного шляху з розрахунком базової архітектури ігрового простору - Грінько, К. О. (ХНУРЕ, 2019)
Augmented reality (AR) is an interactive experience of a real-world environment where the objects that reside in the real-world are "augmented" by computer-generated perceptual information, sometimes across multiple sensory modalities, including visual, auditory, haptic, somatosensory, and olfactory. The given work is devoted to the modern developments in the field of game development regarding path finding in dynamically shaped Augmented Reality space at runtime using Unity Engine with ARCore